Be Careful What You Wish For: Pending Privatization of Australian Higher Education - Welch, Anthony (International Higher Education, 2014)
Australia’s new conservative government is planning some dramatic changes, including the “marketization” of higher education and freeing of universities to charge any tuition they wish. This article discusses the likely consequences of these proposed policies.